The Evaluation of Interior Design Elements in the Library of Islamic University of Malang. - Debri Haryndia Putri (Jurnal VOK@SINDO, 2017)
The interior design is a layout planning and design of the space inside the building. The existence of interior design aims to meet basic human needs of shelter and protection, in addition to the interior design also affects the outlook, the mood and personality of the inhabitants. Therefore an ideal library should pays attention to the order of the interior, but not many libraries developers want to set aside funds for the development of interior design, most of the funds allocated to increase the collection. The good interior design library, will lead visitors to the library to feel comfortable, safe, and productive. The purpose of this study is determine whether or not the influence of the interior design to the comfort of the user in the library of the State Islamic University of Malang, as well as interior design variables determine the dominant influence on the user's convenience in the library of the State Islamic University of Malang. To determines the needs of users of this research using questionnaires. By using questionnaires, the user needs can be mapped and analyzed. In addition, the authors also conducted a study of the literature on the interior of the library as well as direct observation in the Library of the State Islamic University Malang. From this analysis the authors draw the conclusion that from the fifth interior design elements studied were visual elements, flexibility, comfort socialize, thermal and acoustic, Library UIN Malang not pay attention to interior design to developthe library. The highest element score is a visual element with a total mean score of 3.78 (scale of 5).